Developing an electric keyboard cleaner as an innovative alternative design - Nensi, Sri Wahyu; Aulia, Yunita; Mansyur, Doly; Sahroni, Taufik Roni (Universitas Sultan Ageng Tirtayasa, 2023)
It is crucial to maintain cleanliness on our desks and portable tools, such as computers, to prevent dust and other debris accumulation. This practice is essential for uninterrupted usage and to avoid expensive repair costs. A dusty keyboard, with debris lodged between the keys, can significantly disrupt work, hinder keyboard performance, and necessitate time-consuming cleaning. Dust accumulation poses the risk of damaging computer components. Regular computer cleaning ensures optimal and seamless functionality. This research details the development of a portable keyboard cleaner, presenting an innovative design aimed at removing dust and dirt from computers and laptops. The industrial design concept employs the Quality Function Deployment (QFD) method. The process begins with a questionnaire stage to gather customer needs, followed by material selection, consideration of anthropometric data, fabrication, and testing. The manufacturing process utilizes 3D manufacturing for the main components. Final testing involves directly cleaning a laptop keyboard to verify the tool's effectiveness. The research results have led to a product meeting customer needs as per the questionnaire, addressing aspects like ergonomics, materials, durability, safety, cost, among others. The study also recommends an affordable price range, considering estimated returns on investment, anticipating a favorable reception in the market.